(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study was conducted to investigate the effect of addition of different levels of commercial inoculant of lactic acid Bacteria (Ecosyl), 0, 1×105 and 1×106 cfu/g wet material and 4 levels of debis as a source of soluble sugars, 4, 6, 8 and 10% on dry matter (DM) basis on fermentation of wheat straw silage. Urea was added to all samples at rate of 1%. Results revealed that addition of inoculant improved (P<0.01) silage fermentation, where, lower pH (3.97) and ammonia nitrogen (NH3-N) concentration (0.89% of total N) and higher lactic acid (LA) and total volatile fatty acids (VFA) concentrations (7.86 and 1.74% of DM, respectively) were recorded in samples of wheat straw silages prepared with addition of high level of inoculant. However, it also reduced the residual of water soluble carbohydrates (WSC) in these samples. Results also revealed that there was a significant (P<0.01) reduction in pH with increasing level of debis from 4 to 6, 8 and 10%, values were 4.86, 4.90, 4.70 and 4.51, respectively. A significant (P<0.01) reduction was also shown in the residual of WSC, values were, 2.69, 2.82, 2.23 and 4% of DM in samples of wheat straw silage prepared with addition of debis at rate of 4, 6, 8 and 10% respectively. Similar significant effect due to increasing level of debis was also observed in VFA concentrations. Results of this study showed that all parameters of silage fermentation except that of total VFA were significantly (P<0.01) affected by interaction between levels of inoculant and source of soluble sugars.